Schottky-Barrier-Dependent Electrical Characteristics in Conjugated Polymer Transistors With Various Contact Metals - Xu, Yang; Huang, Fanming; Li, Wenwu (Frontiers in Materials, 2020)
Despite the intensive study on the promotion of device performance, the device physics regarding the effects of Schottky barrier on the charge injection in conjugated polymer transistors still need more discussions. Here, the indacenodithiophene–co-benzothiadiazole (IDT-BT) organic field-effect transistors (OFETs) with four different contact metals (Pt, Au, Cu, and Cr) were fabricated to explore the effects. Different Schottky barriers were achieved with the contact electrode’s work function (WF) varying. The ION/IOFF ratio of IDT-BT OFETs increases from 103 to 106 as the WF increases from 4.6 to 5.65 eV. The hole mobility also increases from 0.01 (for Cr) to 2.79 cm2V–1s–1 (for Pt) when the WF approaches the highest occupied molecular orbital (HOMO) level of the conjugated polymer. Moreover, the threshold voltage and subthreshold swing of the devices both decrease with increasing the WF. These could be ascribed to the lowered Schottky barrier with WF, which promotes charge injection. The lowest Schottky barrier (0.123 eV) and contact resistance (1.06 × 104 Ω⋅cm) can be achieved in the devices with Pt contacts, owing to the highest work function.